Peran Praktek Agroforestri Kopi terhadap Iklim Mikro dan Sifat Fisik Tanah di Desa Lanjan Jawa Tengah - Effendi, Mokhtar; Ash Shidiqi, Moh Hasbi; Nurmala Sari, Eka; Arafat, Septrial; Sanjaya, Refki (AgriMalS, 2025)
The increase in the earth's temperature causes extreme climate change which affects the microclimate around plants. Practice of agroforestry is increasingly recognized as an effective land management system that integrates forestry species with agricultural crops to enhance ecological and economic functions. This study focuses on evaluating the role of coffee-based agroforestry practices on microclimate elements and soil physical properties in Lanjan Village, Central Java. The research is driven by the need to understand how shade trees in agroforestry systems influence environmental conditions and support sustainable agriculture, particularly in coffee cultivation. A field-based experimental approach was employed, involving observations and measurements of microclimatic parameters (temperature and humidity) and soil physical characteristics (bulk density). The formulated hypothesis posits that agroforestry practices significantly alter the microclimate and physical characteristics of the soil. The findings confirm that agroforestry has a substantial impact on shaping key microclimatic elements, notably by reducing ambient air temperature and increasing air humidity under tree shade. Additionally, the system exhibits a statistically significant influence on bulk density, indicating an improvement in soil structure and potential for enhanced fertility. Overall, the research highlights that agroforestry systems not only support crop productivity but also contribute positively to microclimate regulation and soil physical health. These insights underscore the importance of integrating shadeas a sustainable land management strategy, particularly in regions experiencing climate variability and soil degradation.